Econovation : the red, white, and blue pill for arousing innovation - Faktor, Steve, 1973- (John Wiley & Sons, 2012)
"The only book you'll need to succeed in our tumultuous economic environment. Over the last twenty years, China fed our zombie-like appetite for iPhones, Prada, and Snuggies. At the same time, its biggest customer, the United States, found itself in debt, under-educated, and covered with recreational tattoos. So now what? Will America wallow in mediocrity like Greece or some C-list celebrity? Or, will our legendary ingenuity save us from Tweeting, and eating, our way to irrelevance?Econovation is a bold, witty response to those questions that doesn't rely on miracles or government for answers. It challenges business leaders to think differently about the next decade of the U.S. economy and respond with big, sustainable innovations. Written by Steve Faktor, Vice President of Growth and Innovation at American Express, Econovation is a trends book on steroids. It's bursting with practical, thought-provoking ideas no executive, entrepreneur, or Fed Chairman can afford to miss. Econovation finds real-world opportunities in unexpected places. Reveals how to capitalize on a market that will go from making nothing to making everything--for China Details psychological pricing and some crafty tricks from Google to reduce reliance on tapped-out consumers Explores how to seduce a desperate government to finance your business, then feed you pancakes in the morning Discusses how to sell to new consumer identities that are based on what people produce, not what they buy, click, or super-size Addresses how to motivate tomorrow's employee with social currency instead of the green, depreciating kind Explains how to upgrade your kids and your business with a little help from Mormons and kindergartners with hacksaws Econovation is a fresh perspective on a future we've taken for granted. It empowers readers to think big, dream big, and conquer economic conditions that paralyze others. With a hefty dose of data, humor, and actionable ideas, Econovation offers insight and amusement in one convenient place--a rare treat for a business book"--Provided by publisher